Discovery of myosin light chain kinase gene variant in a patient with tetralogy of Fallot suffering aortic dissection: Implications for pathogenesis and the role of family and population screening - Radoslaw Debiec; Armia Ebeid; Stephen Hamby; Odeta Anciunaite; Anne Illsley; Ali Nizam; Madiha Iqbal; Kassem Safwan; Tariq Saifullah; Frances Bu’Lock; Toru Suzuki; Nilesh J. Samani; et al. (International Journal of Cardiology Congenital Heart Disease)
Background: Thoracic aortic dissection (TAD) is an uncommon complication in patients with Tetralogy of Fallot (TOF). Information concerning risk factors for TAD in patients with TOF is very limited. Methods: We report a case of Stanford type A TAD in a female patient with previously repaired TOF. Whole exome sequencing (WES); Novogene UK, Agilent V6 capture kit, Illumina HiSeq 100x depth) was performed to identify genetic variants in genes known to be associated with TAD. A systematic literature review was performed in the NCBI PubMed database to identify case reports of TAD in patients with TOF. Results: The patient was a 31-year-old female who developed Stanford type A aortic dissection having had TOF repair at the age of four years. The thoracic aorta was only minimally dilated (sinus of Valsalva 43 mm) on clinical review 16 months prior to TAD. Of note the patient had completed pregnancy 5 months prior to the dissection. There were no other high-risk features predisposing to TAD. WES identified rare genetic variant in a gene previously associated with TAD: MYLK (p.Arg1405His). The literature review identified nine other case reports of TAD in patients with TOF. The reported patients, had no clinical characteristics that distinguished them from the wider population of patients with TOF. Conclusions: The presence of a rare genetic variant in MYLK is a plausible explanation for the clinical presentation. The variant will need further verification to confirm pathogenicity. Pathogenic MYLK variants have been previously reported in context of dissection with minimally dilated aortas.